EFFECT OF CAFFEINE AND VITAMIN D3 ON PROLIFERATIVE AND HYPERTROPHY ZONES OF EPIPHYSEAL CARTILAGE OF MICE FEMUR: Caffeine and Vitamin D3 - Khan, Maimoona; Abdullah, Muhammad Saad; Ambreen, Faiza; Qamar, Khadija (Pakistan Armed Forces Medical Journal, 2018)
Objective: To determine the effect of caffeine and vitamin D3 on the height of proliferative and hypertrophyzones of epiphyseal cartilage of developing femur of BALB/c mice.Study Design: Laboratory based randomized control trial.Place and Duration of Study: The study was conducted at anatomy department, Army Medical College (AMC),Rawalpindi, in collaboration with National Institute of Health (NIH), Islamabad from Oct 2014 to Oct 2015.Material and Methods: A total of thirty (30) BALB/c mice (15 male, 15 female), three weeks old and weighing12-14 g, were taken and divided in to three equal groups of 10 mice each (5 male, 5 female). The control group G1was given normal diet with water ad libitum. In addition to the same diet, animals in experimental group G2were given 10 mg of caffeine per 100 g body weight once a day on alternate days through oral gav age for 60days. All animals of group G3 for 60 days were given caffeine 10mg/100gm body weight on alternate day andvitamin D3 0.1μg per day by oral gav age. At completion of the experiment, effect of caffeine and vitamin D3 onthe height of proliferative and hypertrophy zones of epiphyseal cartilage of mice's femur was analyzed.Results: The mean ± SD of height of proliferative and hypertrophy zones of control group G1 animals was foundto be 31.5 ± 4.1μm and 43 ± 2.6μm, respectively. The mean ± SD of height of proliferative and hypertrophy zonesof experimental group G2 animals was observed as 59 ± 3.2μm and 72.5 ± 7.2μm, respectively. The mean ± SD ofheight of proliferative and hypertrophy zones of experimental group G3 animals was measured as 46 ± 4.6μmand 54 ± 4.6μm, respectively.Conclusion: Caffeine intake altered the height of proliferative and hypertrophy zones of the epiphyseal cartilageof developing femur; however treatment with vitamin D3 ameliorated this effect.